Attenuation of Influenza A Virus mRNA Levels by Promoter Mutations - Fodor, Ervin (American Society for Microbiology, 1998)
We have engineered influenza A/WSN/33 viruses which have viral RNA (vRNA) segments with altered base pairs in the conserved double-stranded region of their vRNA promoters. The mutations were introduced into the segment coding for the neuraminidase (NA) by using a reverse genetics system. Two of the rescued viruses which share a C-G→A-U double mutation at positions 11 and 12′ at the 3′ and 5′ ends of the NA-specific vRNA, respectively, showed approximately a 10-fold reduction of NA levels. The mutations did not dramatically affect the NA-specific vRNA levels found in virions or the NA-specific vRNA and cRNA levels in infected cells. In contrast, there was a significant decrease in the steady-state levels of NA-specific mRNAs in infected cells. Transcription studies in vitro with ribonucleoprotein complexes isolated from the two transfectant viruses indicated that transcription initiation of the NA-specific segment was not affected. However, the majority of NA-specific transcripts lacked poly(A) tails, suggesting that mutations in the double-stranded region of the influenza virus vRNA promoter can attenuate polyadenylation of mRNA molecules. This is the first time that a promoter mutation in an engineered influenza virus has shown a differential effect on influenza virus RNA transcription and replication.